Attitudes to the Green Transition and Willingness to Pay in Emerging Markets: Concerned but Not Paying - Pablo García Guzmán; Zsóka Kóczán (Financial and Economic Review)
While individuals in emerging markets are concerned about climate change, such concerns do not necessarily translate into a willingness to pay for environmental policies. Using rich data for 37 economies, mostly from emerging markets in Europe, the Caucasus, Central Asia and parts of North Africa and the Middle East, we empirically examine correlations with willingness to pay for environmental policies. We show that, beyond ability to pay, people who expect to be better off in the future, who are more patient and who trust the government are all more likely to be willing to pay for policies that mitigate climate change. Our results thus suggest that measures that increase people’s incomes, build trust in government, reduce corruption and increase the transparency and efficiency of government spending could help boost support for green policies. Policies may also receive greater support if they take the form of subsidies, where the costs in terms of higher taxes are less salient.